2009
DOI: 10.1186/1472-6963-9-14
|View full text |Cite
|
Sign up to set email alerts
|

An emergency clinical pathway for stroke patients – results of a cluster randomised trial (isrctn41456865)

Abstract: Background: Emergency Clinical Pathways (ECP) for stroke have never been tested in randomized controlled trials (RCTs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 21 publications
0
66
1
Order By: Relevance
“…[7][8][9] Therefore, improving the communication between EMDs and callers to increase the likelihood that stroke is recognised would promote the initiation of the pre-hospital pathways that are known to expedite patients' access to specialist assessment and treatment. 27 There is evidence to suggest that the EMSs are more likely to be contacted by the public for suspected stroke if the person's symptoms include speech problems, weakness, decreased level of consciousness and dizziness/loss of co-ordination. 28 There is less evidence of an association between the different types of stroke symptoms and the response of the EMSs.…”
Section: -18mentioning
confidence: 99%
“…[7][8][9] Therefore, improving the communication between EMDs and callers to increase the likelihood that stroke is recognised would promote the initiation of the pre-hospital pathways that are known to expedite patients' access to specialist assessment and treatment. 27 There is evidence to suggest that the EMSs are more likely to be contacted by the public for suspected stroke if the person's symptoms include speech problems, weakness, decreased level of consciousness and dizziness/loss of co-ordination. 28 There is less evidence of an association between the different types of stroke symptoms and the response of the EMSs.…”
Section: -18mentioning
confidence: 99%
“…21 The aim of the trial was to assess the impact of an Emergency Clinical Pathway (ECP) for acute stroke patients. The study involved both emergency medical services (EMS) and emergency departments.…”
Section: Prehospital and Disaster Medicinementioning
confidence: 99%
“…In the intervention group 8 of 44 (18.2%) were receiving thrombolysis, and in the control group 0 of 22 (0%) were In the ECP study, the outcome of interest was time from callto-hospital for EMS suspected stroke patients. 21 This analysis used data from the "metropolitan area" where the distance to the hospital did not differ much. The intervention group spent four minutes less time during the transport (p < 0.05).…”
Section: Prehospital and Disaster Medicinementioning
confidence: 99%
“…Therefore, our results agree with other studies in this subject. Luca and colleagues investigated transfer time after and before training course for technicians on stroke and reported its decline from 31.8 to 35.8 minutes [62]. Harbison et al reported that an accurate diagnosis could assist in rapid transfer to appropriate medical center.…”
Section: Discussionmentioning
confidence: 99%